The effect of shoes on knee kinetics and anterior tibial translation during single-leg landing - Hong, Y. N.; Jeong, J.; Lee, S.; Yoon, Y. J.; Shin, C. S. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to compare how knee kinematics and kinetics are influenced during single-leg landing in shod condition compared to barefoot condition. We hypothesized that the anterior tibial translation (ATT) and utilized coefficient of friction (uCoF) are greater in shod landing. Ten male subjects performed single-leg landing from a 0.3-m-high platform using their self-selected dominant lower limb under shod and barefoot condition. A force plate and a motion capture system were used for measuring ground reaction force and capturing kinematics data, respectively. The shod condition showed a significant higher ATT (p = 0.011) and uCoF (p = 0.022) at 30° flexion than barefoot condition. These findings would be considered as one of evidence that high shoe-surface friction increase ACL injury risks due to high ATT at extended knee position.